Is a covered stent justifiable in the treatment of coronary artery perforation? An observational analysis of long‐term results of two different covered stent types. Issue 3 (2nd October 2018) - Rosseel, Liesbeth; Scott, Benjamin; Prihadi, Edgard; Azzano, Alessia; Degrauwe, Sophie; Verheye, Stefan; Convens, Carl; Vermeersch, Paul
Abstract: Objectives: In this retrospective observational study, we investigate outcome of patients treated with or without covered stent (CS) implantation in the management of coronary artery perforation (CAP) during coronary intervention. Background: CSs have shown to be effective devices to achieve acute hemostasis in large CAP. However, doubts have been raised regarding their long‐term outcome. Methods: Data of 19 061 PCI procedures during a 10‐year period were reviewed. Fifty‐five cases of large CAP were withheld (Ellis type 2, 3 or cavity spilling). All medical and procedural records of these cases were retrospectively reviewed. Results: Twenty‐four (43.6%) patients were treated with CS implantation (15 polytetrafluoroethylene and 9 pericardium CSs). Twenty‐six (47.3%) patients were managed without CS implantation, of whom five had unsuccessful delivery of a CS (stent delivery failure 17.2%). Although significantly more Ellis type‐3 perforations were present in the CS group compared to the Non‐CS group (75.0% vs 45.2%; P = 0.03), in‐hospital mortality was not significantly different (8.3% vs 6.4%; [ P = 0.79]). We observed a high rate of CS restenosis (29.2%) but a lower rate of CS thrombosis (4.2%). Despite these observations, 5‐year MACE and all‐cause mortality were not significantly different between CS and Non‐CS group (respectively, 58.8% vs 50.0% ( P = 0.26) and 26.7% vs 13.3% ( P = 0.36)). Conclusion: Although deliverability of CSs was not flawless and a high rate of CS restenosis appeared, short‐ and long‐term outcome were comparable between patients treated with or without CS. Therefore, CSs are justifiable in the treatment of CAP.